PENGARUH MAJALAH INTERNAL TERHADAP RUTINITAS MINAT BACA KARYAWAN PT KCI JABODETABEK - Yanuar, Irfan; Saripudin, Muhammad; Pradana Sumbodo, Yama; Fajar Meirawan, Rizky (Inspiratif Pendidikan, 2023)
Magazine is one of the writings which contains information that is hotly discussed. To write a magazine, you have to use good and correct grammar. Presenting information that is solutive is indeed one of the indications to attract readers' interest in magazines. The aim of the study was to find out whether employee opinions related to the quality of information and the scope of the news had an effect on employees' routines in reading internal magazines at Pt X. This study used quantitative methods to analyze and process data in the form of numbers using the self-report questionnaire (SRQ) method. Through the SRQ method, individual respondents answered all questions independently using the G-Form platform to process data analysis in statistical tests. Based on research conducted for Internal Magazines on Employee Reading Interest Routines at PT X. namely internal magazines that are informative can influence employees' reading interest routines. And information in internal magazines covering all activities within the company does not affect PT X employees' reading interest. And it can be concluded that employees' routines in reading internal magazines are influenced by the quality of the information. The better the quality of the information, the higher the employee's reading routine.